Forest giants on different evolutionary branches: Ecomorphological convergence in helicopter damselflies*. (19th February 2019) - Toussaint, Emmanuel F. A.; Bybee, Seth M.; Erickson, Robert J.; Condamine, Fabien L.
Abstract: The convergent evolution of analogous features is an evolutionary process occurring independently across the tree of life. From the evolution of echolocation, prehensile tail, viviparity, or winged flight, environmental factors often drive this astonishing phenomenon. However, convergent evolution is not always conspicuous or easily identified. Giant damselflies count among the largest flying insects on Earth, and have astonishing ecologies including orb‐web spider plucking and oviposition in phytotelmata. One species occurs in the Afrotropics and 18 species are found in the Neotropics. Convergent evolution was historically hypothesized based on the ecological and morphological affinities of these two geographically distant lineages but was not supported by earlier phylogenetic inferences supporting their monophyly. Using a molecular supermatrix approach and a large selection of outgroups, we revisit and reject the monophyly of Afrotropical and Neotropical giant damselflies that is otherwise supported by a morphological phylogeny. Molecular divergence time estimation suggests an origin of Afrotropical giant damselflies in the late Paleogene, and of Neotropical ones at the Cretaceous/Paleogene boundary, thereby rejecting a long‐standing West Gondwana vicariance hypothesis. The strong ecological and morphological resemblances between these two independent lineages represents an astonishing case of Amphi‐Atlantic tropical convergent evolution.